Early Aptian paleoenvironmental evolution of the Bab Basin at the southern Neo‐Tethys margin: Response to global carbon‐cycle perturbations across Ocean Anoxic Event 1a. (29th April 2013) - Yamamoto, Kazuyuki; Ishibashi, Masatoshi; Takayanagi, Hideko; Asahara, Yoshihiro; Sato, Tokiyuki; Nishi, Hiroshi; Iryu, Yasufumi
Abstract: [1] Lower Aptian carbonates in the Bab Basin at the southern Neo‐Tethys margin record significant environmental changes across Oceanic Anoxic Event 1a (OAE1a). A long‐lasting negative shift of carbon‐isotope ratios (δ 13 C) associated with a distinct decrease in oxygen‐isotope ratios (δ 18 O) in orbitolinid‐rich carbonates characterizes the onset of OAE1a (Livello Selli), supporting a hypothesis that a long‐lasting volcanic CO2 emission is the main cause of OAE1a, inducing global warming. A bloom of microencrusters ( Lithocodium and Bacinella ) across the proto–Bab Basin occurred synchronously at the beginning of the subsequent positive δ 13 C excursion, responding to the global carbon‐cycle perturbations. The carbonates, formed during the OAE1a, show higher strontium‐isotope ratios ( 87 Sr/ 86 Sr) compared with those of global seawater; this was likely caused by a local influx of isotopically heavier strontium, along with nutrients, into the proto–Bab Basin. These biotic proliferations were triggered by an increased nutrient supply induced by intensified continental weathering due to the global warming suggested by the increase in δ 18 O values. Spatial variations in the δ 13 C values among sites in the Bab Basin and its surrounding platform are related to local environmental factors, such as the degree of mixing of basin water with ocean water and local removal of 12 C by metabolic activity at the platform‐top. The δ 13 C profile of the studied core indicates global removal of organic carbon of OAE1a began during the early stage of the second‐order transgression and lasted until the early stage of the highstand after the OAE1a. The Livello Selli corresponds to the early stage of this transgression. Key Points: Establishing high‐resolution d13C profile of carbonates deposited during OAE1a Delineating biotic response to environmental changes during OAE1a Showing OAE1a is a long lasting event during the second‐order transgression